2017
DOI: 10.1049/el.2017.1499
|View full text |Cite
|
Sign up to set email alerts
|

Inductive loaded compact monopole antenna for ultra‐wideband applications

Abstract: An effective method to design an ultra-wideband antenna using a vertical narrow strip element is described. The proposed low profile antenna has good radiation characteristics such as polarisation purity, omnidirectional radiation pattern and good efficiency over the entire band of operation, which are the most desirable characteristics required for a wireless system to operate in the present high interference environment. The designed antenna has a measured return loss of below −10 dB and low cross polarised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…An inductor added in series between the radiating strips provides another degree of freedom to control the span of distribution of the resonant frequencies. It is reported that the series inductors merge the distributed multiple resonance bands into a single band [8]. The designed layout of the two‐strip inductive‐loaded stepped‐impedance printed monopole antenna is shown in Fig.…”
Section: Proposed Theoretical Design Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…An inductor added in series between the radiating strips provides another degree of freedom to control the span of distribution of the resonant frequencies. It is reported that the series inductors merge the distributed multiple resonance bands into a single band [8]. The designed layout of the two‐strip inductive‐loaded stepped‐impedance printed monopole antenna is shown in Fig.…”
Section: Proposed Theoretical Design Approachmentioning
confidence: 99%
“…Monopole antennas with inductive loads are reported to have increased resonance bandwidths [5–7]. Recently, it has also been validated that the use of lumped inductors combine the multiple bands of resonance of the printed stepped‐impedance monopoles into a single resonance band encompassing the entire UWB range of frequencies [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous miniaturization techniques have been developed and successfully implemented by several researchers for different types of antennas. [6][7][8][9][10][11][12] For dipole and monopole antennas, some of the techniques include material loading, 6 impedance loading, 7 folding shape like a fractal and spiral meander lines. 8,9 For patch antennas, the techniques consist of shorting plates or posts, 10,11 creating different types of slots 12 and loading with high permittivity dielectric substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, printed monopole/UWB antennas in planar design have received much attention among the wireless industry. It is because of their high data rate communication in short range, with low power signals . Moreover, these UWB antennas are showing their potential applications in ultrawideband radios, internet of things (IOT) devices, Bluetooth, WLAN/WiMAX, and other UWB communication systems .…”
Section: Introductionmentioning
confidence: 99%